Increasing Students' Knowledge Regarding Clean and Healthy Living Behavior Through Counseling at SDN Kedung Pedaringan II Kepanjen, Malang Regency - Rahman, Ibrahim Khalil; Nafiisah, Adilah; Wardani, Aradea Putri Ayu; Saidah, Dinda Auliyatus; Liza, Diva Natasya (Tarqabin Nusantara Group, 2024)
Perilaku Hidup Bersih dan Sehat (PHBS) is essential for everyday life and can be implemented in various settings. Schools, as influential institutions, have a crucial role in shaping students' clean and healthy living behavior. This study aimed to enhance students' knowledge of PHBS and their willingness to practice it in school. We conducted a quantitative survey using a One Group Pre-test and Post-test design, involving all students from grades 1 to 5 at SD Negeri Kedung Pedaringan 2 in Malang Regency. Observations revealed that some students already practiced certain aspects of PHBS, such as handwashing and proper waste disposal, albeit without recognizing their connection to a Clean and Healthy Lifestyle. To address this, we provided educational materials, using posters for grades 1-3 and PowerPoint presentations for grades 4 and 5. The engaging materials captured the students' interest, and they actively participated, including singing about PHBS. Post-tests indicated a significant increase in their knowledge and enthusiasm for implementing PHBS. In conclusion, PHBS is vital in everyday life, particularly within the school environment. This study emphasized the role of teachers in guiding students and fostering strong teacher-student relationships. By promoting PHBS, schools can become cleaner, healthier, and disease-free environments. Future research should delve deeper into enhancing students' understanding and interest in their school's PHBS environment. The hope is that such efforts will continue to improve the cleanliness and health of school environments, ultimately benefiting students and the community as a whole.